PENGARUH TRANSFER PRICING, THIN CAPITALIZATION DAN TAX HAVEN TERHADAP PENGHINDARAN PAJAK DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022) - Ainaya Annastasya; Ristiyana, Rida; Kristanti (Journal Accounting International Mount Hope, 2025)
This study aims to determine the effect of Transfer Pricing, Thin Capitalization and Tax Haven on Tax Avoidance with Institutional Ownership as a Moderating Variable. This type of research is quantitative using secondary data. The research population is manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period with a population of 195 companies. The sampling technique used purposive sampling technique with a total sample of 28 companies. The data analysis method used is panel data regression using E-Views version 12 software. The results of this study show that Transfer pricing, Thin Capitalization and Tax Haven have a simultaneous effect on tax avoidance. transfer pricing, tax haven and institusional ownership has no significant effect on tax avoidance. Thin Capitalization has a positive and significant effect on tax avoidance. Institutional ownership is unable to moderate the influence of transfer pricing, thin capitalization and tax havens on tax avoidance.